2009
DOI: 10.1080/09638280902751949
|View full text |Cite
|
Sign up to set email alerts
|

Work stress and work ability: cross-sectional findings from the German sociomedical panel of employees

Abstract: Work stress is associated with restrictions of work ability, but longitudinal analyses are required to confirm a causal relation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 25 publications
5
27
0
3
Order By: Relevance
“…Estudos epidemiológicos indicam a contribuição do estresse psicossocial no trabalho, mensurado por meio dos instrumentos de demanda-controle ou desequilíbrio esforço-recompensa na explicação dos efeitos adversos na saúde 25,26,27 . Além disso, Bethge et al 28 demonstraram o impacto desses estressores físicos e psicossociais na capacidade para o trabalho. Segundo os autores, o risco de uma limitada capacidade para o trabalho foi superior para pessoas com alta demanda e baixo controle no trabalho (odds ratio -OR = 5,62; intervalo de 95% de confiança IC95%: 3,55; 8,89) e com elevado desequilíbrio entre esforço e recompensa (OR = 3,78; IC95%: 2,60; 5,51).…”
Section: Discussionunclassified
“…Estudos epidemiológicos indicam a contribuição do estresse psicossocial no trabalho, mensurado por meio dos instrumentos de demanda-controle ou desequilíbrio esforço-recompensa na explicação dos efeitos adversos na saúde 25,26,27 . Além disso, Bethge et al 28 demonstraram o impacto desses estressores físicos e psicossociais na capacidade para o trabalho. Segundo os autores, o risco de uma limitada capacidade para o trabalho foi superior para pessoas com alta demanda e baixo controle no trabalho (odds ratio -OR = 5,62; intervalo de 95% de confiança IC95%: 3,55; 8,89) e com elevado desequilíbrio entre esforço e recompensa (OR = 3,78; IC95%: 2,60; 5,51).…”
Section: Discussionunclassified
“…The first of two studies of nursing teams (15,22) , with 387 and 269 workers respectively, identified that 83.2% of the employees presented Good work capacity and the second identified that 51.7% presented Good work capacity and 20.1% Excellent. In an international study, 32.0% of the subjects reported Moderate capacity (23) .…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, overcommitment might mediate that relationship; individuals overcommitted to work might underestimate demands and overestimate their coping resources, while failing to perceive work conditions characterized by nonreciprocal exchange [Siegrist, 2008]. The psychological stress that arises from imbalance between efforts and rewards and between demands and control at work has been shown to induce negative effects on work ability Bethge et al, 2009Bethge et al, , 2012Bostr€ om et al, 2012;Prochnow et al, 2013].…”
Section: Introductionmentioning
confidence: 96%